The Survival Rate of Colorectal Cancer in dr. Cipto Mangunkusumo Hospital - Jeo, Wifanto S.; Subrata, Feyona H (The New Ropanasuri Journal of Surgery, 2020)
Introduction. Colorectal cancer (CC) is a malignancy with the third highest incidence and the second cause of death. 1.4 million new cases of colorectal cancer occurred in 2012, increasing to 1.8 million new cases in 2019, with almost 900,000 deaths caused by CC in the world. In Indonesia, there were 30,017 new cases of CC in 2019, with fatalities reaching nearly 16,000 cases. There are differences in the survival rates of the CC between developed countries and Indonesia. This study aims to determine the survival rate of CC patients in Indonesia. Method. A retrospective cohort study design with survival analysis. The study was conducted at the Department of Surgery, Faculty of Medicine, University of Indonesia, RSCM, from January 2014 to December 2016. 316 samples were obtained from the registration of the RSC M CC with the CC who had received therapy according to the stage of cancer they suffered during the period January 2014 to December 2016. Results. The overall five-year survival rate in this study was 43%. The survival rate of colorectal cancer patients aged ≥45 years reached 50% at observation 20 months. Age group(95% CI 44.03-57.32) months, stage III was 38.59 months (95% CI 32.20-44.97), 30.36 months in stage IV subjects (95 % CI 25,638-35.09). the average survival of subjects who received chemotherapy was 38.28 months (95% CI 33.44-43.11). not receiving adjuvant therapy was 33.71 months (95% CI 27.79-39.63). Mean survival of subjects who received definitive surgery (44.39 months; 95% CI 40.35-48.43) and who did not get definitive surgery (20.08 months; 95% CI 15.82-24.36). Conclusion: The overall survival rate of the CC within five years at the RSCM was 43%. Factors that influence patient survival are clinical stage and definitive surgery in primary tumor mass resection